Estimativa da produção de biogás em aterro sanitário municipal no oeste do Paraná - Santos, Rosângela Aparecida Ribeiro (2019)
The landfill is usually the final disposal of organic and inorganic municipal solid waste (MSW). The organic fraction, under anaerobic decomposition, produce biogas and a slurry. The biogas produced by landfill depends on the composition of the waste that is deposited daily. The manure that is collected and subsequently goes to the treatment stage also contains an organic fraction that can be converted into biogas. In this work, the biogas production of a landfill was evaluated by means of a mathematical model, to estimate the production of the solid part, and, by laboratory analysis, the methanogenic potential of the collected slurry. The methodology of the Intergovernmental Panel on Climate Change (IPCC) was used to estimate biogas production of MSW residues. For the slurry, batch tests were carried out under controlled conditions to obtain the methanogenic potential and the composition of the same. From the IPCC model it was possible to estimate a production of 0.27260 Gg year-1 or 380,299. 2 m3 year-1 of biogas. From the laboratory assays a yield of 333 LNCH4 gVS-1 was obtained. The composition of the biogas obtained from the slurry was 58.1% for CH4 and 20.6% for CO2. This study demonstrated that the biogas generated from the leachate collected can be an important source of renewable energy generation.